Percutaneous Coronary Intervention: Developments in the Last 12 Months - Rhian E Davies; J Dawn Abbott (US Cardiology Review)
In 2018, there were several studies that significantly added to the field of interventional cardiology. Research was focused on understanding the role of percutaneous coronary intervention (PCI) in various clinical syndromes, optimizing outcomes for high-risk lesion subsets, and building an evidence base for greater adoption of PCI guided by physiology and intracoronary imaging. In the area of innovation, novel and iterative developments in drug-eluting stents (DES) and scaffold platforms were compared with current generation DES. This article summarizes the research from last year which has had the most impact on PCI techniques and clinical care.